Potencial modulador da própolis marrom de araucária sobre o processo inflamatório, analgesia e artrite reumatoide - Pereira, Poliana Marques (2022)
Brown propolis is a balsamic and resinous material, being found throughout the Brazilian territory, especially in the South and Southeast regions. Knowing that the chemical composition of brown propolis can change according to the place and botanical origin from which it is collected, this work aims to evaluate the mechanical and thermal hyperalgesia activity, the anti-inflammatory and arthritis potential, and the toxicological profile, of Araucaria brown propolis obtained in the thematic project (2017/04138-8). Hyperalgesia was evaluated for mechanical and thermal sensitivity with and without an inflammatory process. Anti-inflammatory activity was evaluated by cell volume and migration in carrageenan-induced paw edema. Collagen-induced rheumatoid arthritis was assessed by mechanical and thermal nociception at the plantar surface, and mechanics at the femorotibial and caudal joints, assessment of plantar volume, histopathological assessment of tail structures, and radiography. Toxicity was assessed by laboratory tests for AST, ALT, creatinine and urea, and weight assessment. The results show that brown propolis has effective anti-inflammatory activity at a dose of 90 mg/kg, and this effect may be associated with prostaglandin inhibition. In addition, it has an effect on mechanical nociception mediated by the inhibition of the inflammatory process. Brown propolis at a dose of 90 mg/kg showed potential for the treatment of arthritis observed by mechanical analgesia in the femorotibial and caudal joints, by evaluating the femorotibial and caudal joint space and by reducing the plantar volume. Propolis, at the doses tested, showed no hepatotoxicity and nephrotoxicity. In this way, this work seeks to contribute to a better understanding of the action of Araucaria brown propolis, allowing to add value to the product and explore its marketing potential, in addition to greater safety and effectiveness in future clinical uses. KEYWORDS: CIA; Carrageenan; Nociception; Ethnopharmacology